Characterization of Two Unique Cold-Active Lipases Derived from a Novel Deep-Sea Cold Seep Bacterium - Chenchen Guo; Rikuan Zheng; Ruining Cai; Chaomin Sun; Shimei Wu (Microorganisms, 2021)
The deep ocean microbiota has unexplored potential to provide enzymes with unique characteristics. In order to obtain cold-active lipases, bacterial strains isolated from the sediment of the deep-sea cold seep were screened, and a novel strain gcc21 exhibited a high lipase catalytic activity, even at the low temperature of 4 °C. The strain gcc21 was identified and proposed to represent a new species of Pseudomonas according to its physiological, biochemical, and genomic characteristics; it was named Pseudomonas marinensis. Two novel encoding genes for cold-active lipases (Lipase 1 and Lipase 2) were identified in the genome of strain gcc21. Genes encoding Lipase 1 and Lipase 2 were respectively cloned and overexpressed in E. coli cells, and corresponding lipases were further purified and characterized. Both Lipase 1 and Lipase 2 showed an optimal catalytic temperature at 4 °C, which is much lower than those of most reported cold-active lipases, but the activity and stability of Lipase 2 were much higher than those of Lipase 1 under different tested pHs and temperatures. In addition, Lipase 2 was more stable than Lipase 1 when treated with different metal ions, detergents, potential inhibitors, and organic solvents. In a combination of mutation and activity assays, catalytic triads of Ser, Asp, and His in Lipase 1 and Lipase 2 were demonstrated to be essential for maintaining enzyme activity. Phylogenetic analysis showed that both Lipase 1 and Lipase 2 belonged to lipase family III. Overall, our results indicate that deep-sea cold seep is a rich source for novel bacterial species that produce potentially unique cold-active enzymes.